Control of triboelectricity by mechanoluminescence in ZnS/Mn-containing polymer films. (December 2021) - Wang, Nannan; Pu, Mingjie; Ma, Zhidong; Feng, Yange; Guo, Yufeng; Guo, Wanlin; Zheng, Youbin; Zhang, Liqiang; Wang, Zhaofeng; Feng, Min; Li, Xiaojuan; Wang, Daoai
Abstract: The electrostatic generated during the contact charging process seriously affects the areas of electronics, pharmaceutics, and aerospace engineering, among others. Despite remarkable progress, almost all antistatic surfaces suffer from notable limitations. The regulation of energy and electron transfer during friction is a new strategy to control the accumulation of surface interfaces. In this study, a new method to control the release of triboelectric charges on polymer surfaces by interconversion between triboelectricity and mechanoluminescence (ML) has been proposed. In this method, the tribocharges are mitigated when ML is generated in the presence of a mediator, i.e., ZnS:Mn. Meanwhile, the presence of tribocharges increases ML intensity. Results show that when 10% ZnS:Mn is added and ML is generated, the current and voltage of ZnS:Mn@PDMS-based TENG are reduced by 96.4% and 94.9%, respectively. Meanwhile, when a charge of 11 nC is present on the surface of the film, the ML intensity increases by 84% compared with the uncharged film. Furthermore, we confirm that the triboelectrons on the polymer surface can easily enter the crystal lattice of ZnS to participate in ML, and the injection of electrons remarkably increases the ML intensity of ZnS:Mn according to the results of density functional theory calculations. This strategy combines triboelectron transfer with ML, and the quantitative relationship between transferred charge and ML intensity has been established through experiments, which has important application prospects in the field of friction characterization and detection. Furthermore, the release of triboelectric charges on the polymer surface is controlled by introducing ML, and the elimination of charges is in situ, which also has potential application prospects in the areas of anti-static and patterning. Graphical Abstract: A new method to control the release of triboelectric charges on polymer surfaces by interconversion between triboelectricity and mechanoluminescence (ML) has been proposed. The triboelectrons on the PDMS surface enter the ZnS lattice and participate in ML, which dissipates the triboelectric charges on the PDMS surface. Furthermore, the triboelectrons entering the ZnS lattice can increase the ML intensity. ga1 Highlights: When 10% ZnS: Mn was added and generated mechanoluminescence (ML), the triboelectricity was reduced by 96.4%. When there was a charge of 11 nC on the surface of the film, the ML intensity increased by 84% . Density functional theory calculations verify the hypothesis.